Synthesis of Lignocellulose-Based Poly(Butylene 3-Propyladipate-Co-Furanoate): Replacing Adipate - Ruijia Hu; Weihao Li; Xi Zhou; Shunmin Yi; Xingfu Zheng; Qiufeng Mo; Wanyu Liu (Molecules)
A novel lignocellulose-based poly(butylene 3-propyladipate-co-furanoate) (PBApF) was synthesized from lignocellulose-derived 3-propyladipic acid (3PAA), 1,4-butanediol (BDO), and 2,5-furandicarboxylic acid (FDCA). The copolyesters were characterized by 1H NMR, GPC, DSC, TGA, XRD, DMA, rotational rheology, tensile tests, and enzymatic degradation tests. They were random copolymers whose composition was well controlled, and the number-average sequence lengths of the copolyesters were around 1.35–4.33. By combining the results of tensile tests and DMA, the elongation at break of PBApF45 (1865%) had a much greater value than that of PBAF45 (1250%), i.e., the branching incorporated into the linear polymer increased the melt strength and conferred tension-hardening properties, which helped to enhance the elongation of the polymer. In addition, the influences of 3PAA content on enzymatic degradation were studied in terms of weight loss; when the content of 3PAA was 55 mol%, the copolyesters exhibited good biodegradability. Thus, depending on their composition, PBApFS might find end applications as biodegradable elastomers or impact modifiers for other polymers.